1997
DOI: 10.1111/j.1432-1033.1997.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemistry of Megasphaera Elsdenii Iron Hydrogenase

Abstract: The Fe-hydrogenase from Megasphaera elsdenii undergoes direct electron exchange with glassy carbon electrodes. Cyclic voltammetry defines the catalytic performance of the enzyme over a continuous but precisely defined range of potentials. In the presence of H, and protons the bias of the enzyme towards H, production is readily visualised. Variation of the response with pH indicates that protein ionisations with pK of approximately 6.7 and 8.3 regulate the catalytic activity. Possible origins for these observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 36 publications
9
75
1
Order By: Relevance
“…114 Glassycarbonwasalsoused,althoughlessfrequently. 144,201,202 Gorton and co-workers tested the adsorption of various laccases on spectrographic graphite and HOPG. 203 Karyakin and co-workers have used electrodes based on carbon filament material and treated with sulfuric acid to adsorb hydrogenases.…”
Section: Attaching the Enzymementioning
confidence: 99%
See 2 more Smart Citations
“…114 Glassycarbonwasalsoused,althoughlessfrequently. 144,201,202 Gorton and co-workers tested the adsorption of various laccases on spectrographic graphite and HOPG. 203 Karyakin and co-workers have used electrodes based on carbon filament material and treated with sulfuric acid to adsorb hydrogenases.…”
Section: Attaching the Enzymementioning
confidence: 99%
“…144,145 Typical "n-values" are in the range 1-2; the greater n cat , the steeper the sigmoid. When the wave shape is not sigmoidal (as often occurs, see e.g.…”
Section: From Phenomenological Equations To Kinetic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[83,84] Whereas in the late 80s, electrochemistry provided essential kinetic data for Hases and their physiological partners, [85][86][87][88] Yoropolov's group, followed by Hagen's then Armstrong's groups demonstrated that Hases could yield a direct current for H 2 oxidation or proton reduction when adsorbed at graphite electrodes. [83,84,88,89] The influences of parameters such as pH, temperature, gas composition, and graphite polishing procedure were evaluated, [89][90][91] before fundamental research was undertaken to understanding of the catalytic properties of this exciting enzyme. Essential kinetic data were then available to support the spectroscopic data.…”
Section: Enzymes For H 2 Oxidationmentioning
confidence: 99%
“…For example, fumarate reductase and succinate dehydrogenase preferentially catalyze opposing reactions (30,31) and are separately regulated and distinct gene products (32,33). In many organisms, H ϩ reduction and H 2 oxidation are catalyzed by separate enzymes with the converse catalytic biases (34,35). Can PFOR serve as an efficient pyruvate synthase or is it prejudiced toward oxidative decarboxylation?…”
mentioning
confidence: 99%